Milano: la riapertura del tratto coperto del naviglio della Martesana - Prusicki, Marco (Ri-Vista. Research for landscape architecture, 2017)
The reopening of the covered stretch of the inland waterway called Naviglio Martesana which flows in Milan is an extraordinary occasion to regenerate via Melchiorre Gioia, a main road, 40 m wide and 2,5 km long: a complex and inhospitable urban space, where the strong contrast between the unity given by its straight course (originated by the sixteenth-century project which was at the base) and the heterogeneity of its formal and functional characters, is immediately perceivable. The project proposes the replacement of the actual underground hydraulic system with a new open channel and a lowered quay, along which local public and commercial activities are envisaged. A real "street in the street", protected from traffic, which continues the bikeway of Naviglio Martesana (about 40 km) as far as Porta Nuova district, reinterpreting in a contemporary way the potentialities of its original Renaissance conception.